KRITIK AL-QUR`AN TERHADAP SISTEM KEPERCAYAAN SINKRETISME - Iwan Satiri; Muhammad Hariyadi (UIN Mataram, 2021)
The conclusion of this dissertation views negatively the pantheistic syncretism belief system with its doctrine of immanence to the stage of belief in incarnation or incarnation, namely believing that God can incarnate in everything. So that this pantheistic syncretism belief system has a very negative impact leading to shirk, because it can formulate and sanctify God's symbols in material form that is contrary to the teachings of monotheism in the Qur'an.